2015
DOI: 10.1074/jbc.m114.602292
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation Is a Conserved Feature of the Early Embryonic Factor Zelda That Requires a Cluster of Four Zinc Fingers for DNA Binding and a Low-complexity Activation Domain

Abstract: Background: Zelda initiates widespread transcription of the zygotic genome during embryogenesis. Results: Zelda binds DNA using C-terminal zinc fingers and activates transcription through a low-complexity domain. Conclusion: Transcriptional activation by Zelda is conserved in insects and uses domains we have identified to bind cisregulatory regions and drive gene expression. Significance: We provide the first insights into the functional domains of the essential activator Zelda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(89 citation statements)
references
References 40 publications
(59 reference statements)
6
81
0
Order By: Relevance
“…Many transcription factors have strong activation domains, putting accessible enhancer regions at risk for unwarranted activation. For example, Zld has high transactivation potential and likely recruits the histone acetyl transferase CBP that mediates H3K27ac (Hamm et al 2015;Stampfel et al 2015), consistent with H3K27ac being present during enhancer priming by Zld (Li et al 2014). Strikingly, we showed that Zld is still bound to DV enhancers during DV patterning, yet these enhancers have no or low H3K27ac and remain uninduced in parts of the embryo.…”
Section: A Role For Repressors In Keeping Poised Enhancers Inactivementioning
confidence: 57%
“…Many transcription factors have strong activation domains, putting accessible enhancer regions at risk for unwarranted activation. For example, Zld has high transactivation potential and likely recruits the histone acetyl transferase CBP that mediates H3K27ac (Hamm et al 2015;Stampfel et al 2015), consistent with H3K27ac being present during enhancer priming by Zld (Li et al 2014). Strikingly, we showed that Zld is still bound to DV enhancers during DV patterning, yet these enhancers have no or low H3K27ac and remain uninduced in parts of the embryo.…”
Section: A Role For Repressors In Keeping Poised Enhancers Inactivementioning
confidence: 57%
“…Instead, Zld binds DNA through a cluster of four zinc fingers in the C terminus (Struffi et al 2011;Hamm et al 2015). In addition, Zld is a large protein with no recognizable enzymatic domains that activates transcription through a low-complexity protein domain (Hamm et al 2015). Thus, Zld likely facilitates open chromatin through interactions with cofactors, and it is possible that recruitment of different cofactors to distinct Zld-bound loci could partially explain the differential requirement on Zld for chromatin accessibility in the early embryo.…”
Section: Genome Research 1721mentioning
confidence: 99%
“…Unlike the pioneer factor FOXA1, which can bind open chromatin by binding through a winged-helix domain (Cirillo et al 1998(Cirillo et al , 2002, the Zld DNAbinding domain does not resemble that of a linker histone. Instead, Zld binds DNA through a cluster of four zinc fingers in the C terminus (Struffi et al 2011;Hamm et al 2015). In addition, Zld is a large protein with no recognizable enzymatic domains that activates transcription through a low-complexity protein domain (Hamm et al 2015).…”
Section: Genome Research 1721mentioning
confidence: 99%
“…Although the exact mechanism by which ZLD mediates BCD hub formation and binding remains unclear, we speculate that a combination of protein-protein interactions facilitated by intrinsically disordered low-complexity domains (Hamm et al 2015) of ZLD and its reported role in promoting chromatin accessibility (Foo et al 2014;Schulz et al 2015;Sun et al 2015) may contribute to BCD clustering (Fig. 4).…”
Section: Formation Of Bcd Hubs In the Posterior Embryo Is Dependent Omentioning
confidence: 99%